The experiences of health-care providers during the COVID-19 crisis in China: a qualitative study - Liu, Qian; Luo, Dan; Haase, Joan E; Guo, Qiaohong; Wang, Xiao Qin; Liu, Shuo; Xia, Lin; Liu, Zhongchun; Yang, Jiong; Yang, Bing Xiang (The Lancet global health, 2020)
In the early stages of the outbreak of coronavirus disease 2019 (COVID-19) in Hubei, China, the local health-care system was overwhelmed. Physicians and nurses who had no infectious disease expertise were recruited to provide care to patients with COVID-19. To our knowledge, no studies on their experiences of combating COVID-19 have been published. We aimed to describe the experiences of these health-care providers in the early stages of the outbreak. We did a qualitative study using an empirical phenomenological approach. Nurses and physicians were recruited from five COVID-19-designated hospitals in Hubei province using purposive and snowball sampling. They participated in semi-structured, in-depth interviews by telephone from Feb 10 to Feb 15, 2020. Interviews were transcribed verbatim and analysed using Haase's adaptation of Colaizzi's phenomenological method. We recruited nine nurses and four physicians. Three theme categories emerged from data analysis. The first was “being fully responsible for patients' wellbeing—‘this is my duty’”. Health-care providers volunteered and tried their best to provide care for patients. Nurses had a crucial role in providing intensive care and assisting with activities of daily living. The second category was “challenges of working on COVID-19 wards”. Health-care providers were challenged by working in a totally new context, exhaustion due to heavy workloads and protective gear, the fear of becoming infected and infecting others, feeling powerless to handle patients' conditions, and managing relationships in this stressful situation. The third category was “resilience amid challenges”. Health-care providers identified many sources of social support and used self-management strategies to cope with the situation. They also achieved transcendence from this unique experience. The intensive work drained health-care providers physically and emotionally. Health-care providers showed their resilience and the spirit of professional dedication to overcome difficulties. Comprehensive support should be provided to safeguard the wellbeing of health-care providers. Regular and intensive training for all health-care providers is necessary to promote preparedness and efficacy in crisis management. National Key R&D Program of China, Project of Humanities and Social Sciences of the Ministry of Education in China.